Technological aspects of de-icing fluids purification and reclaiming process in the airports - Шутько, А. П.; Павлыш, В. Д. (Proceedings of National Aviation University (archive), 2000)
Presented are the results of de-icing fluids use in Ukraine airports. Model of purification and utilization system also block-module unit for collection and reclaiming of de-icing fluids are developed